2018
DOI: 10.1103/physrevb.97.100302
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a topological phase transition in a gyroscopic lattice

Abstract: Topological metamaterials exhibit unusual behaviors at their boundaries, such as unidirectional chiral waves, that are protected by a topological feature of their band structure. The ability to tune such a material through a topological phase transition in real time could enable the use of protected waves for information storage and readout. Here we dynamically tune through a topological phase transition by breaking inversion symmetry in a metamaterial composed of interacting gyroscopes. Through the transition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…4A. We note that this feature was absent in the gyroscopic honeycomb lattice previously studied [4,5], whose topology was unaffected by changes in Ω k and Ω g . This allowed the topology to be continuously connected to the electronic Haldane model, unlike in the spindle lattice.…”
Section: Twisted Spindle Latticementioning
confidence: 61%
See 2 more Smart Citations
“…4A. We note that this feature was absent in the gyroscopic honeycomb lattice previously studied [4,5], whose topology was unaffected by changes in Ω k and Ω g . This allowed the topology to be continuously connected to the electronic Haldane model, unlike in the spindle lattice.…”
Section: Twisted Spindle Latticementioning
confidence: 61%
“…To date, the only ordered lattices that have been considered in this framework are the honeycomb lattice and simple distortions thereof [4,5]. A slightly different manifestation of gyroscopic metamaterials considered in [7] found that by including staggered sublattice precession frequencies and bond strengths, time reversal symmetry could be effectively broken in lattices with square and honeycomb symmetries.…”
Section: The Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of gyroscopic metamaterials [11,13,14] showed that perturbations migrate to the edge of the sample and propagate around the edge in one direction. In our system, for very weak damping or small α m , it would be possible to perturb skyrmions in the bulk of the pinfree channel and obtain motion that is localized on the edges of the channel, producing a transient current which eventually damps away.…”
Section: Discussionmentioning
confidence: 99%
“…Topological mechanics offers a powerful framework for the control of phononic excitations. Topologically pro- tected phonons localized at the edges of gapped mechanical materials have been studied extensively in special lattices [19,20,25,42,43] and in random networks [24,44].…”
Section: Topologically Protected Modesmentioning
confidence: 99%